Structure and performance of cassava markets: challenges of food security and connecting small farmers to markets in Cameroon - Mbarga Evouna, Joseph Serge; Molua, Ernest L.; Djomo Choumbou, Raoul Fani; Kemeni Kambiet, Perez L. (Frontiers in Sustainable Food Systems, 2024)
Agrifood markets play a pivotal role in assuring national food security and improved welfare for smallholder farmers. However, the extent to which this is possible depends on the structure and performance of these markets. This study utilizes primary data from 326 cassava marketers operating in fifteen markets to examine the structure and performance of the cassava market in Cameroon. We employ parametric and non-parametric techniques to determine the degree of market concentration and marketing performance of the cassava marketers. Our findings highlight a high market concentration with a Gini coefficient of 0.76 and 0.79 for wholesalers and retailers respectively. This indicates that the cassava market is probably oligopolistic in structure. In addition, we reveal that average marketing efficiency is 14.20% and 87% for retailers and wholesaler, respectively. This indicates that retailers are relatively inefficient as compared to wholesalers. Furthermore, we observed that prices are set up in the markets according to the place of sale and the type of marketers. Howbeit, prices are influenced by factors such as transport, the quantity sold on spot markets, and the need for liquidity. By and large, our results highlight that the region, type of marketer (wholesaler or retailer) as well as socioeconomic factors account significantly for the variation of odds to participate in markets. Hence, to influence the dynamics of price on the consumers, it might be necessary to set up policies that could improve retailers' efficiency. This might be through restructuring of retailers into cooperatives and associations which may permit retailers to access other critical resources.